Pengukuran Kinerja terhadap Pengaruh Aplikasi E-Manajemen Penyidikan dan Budaya Organisasi dalam Penanganan Perkara Pidana di Polres Teluk Bintuni - juli, mas; Zani, Yelly Febrina; Spalanzani, Widya (Journal of Industrial and Engineering System, 2021)
Police as an institution that has many divisions and staff that require an information system. In the investigation, the Bay of Bintuni Polres Recrement Sat has used the investigation e-management application but has not been adequate. This study aims to find out the existence or absence the effect of e-management application from investigation and organizational culture on investigator performance in handling criminal matters. The study was a quantitative with a research sample of 76 people. Testing hypotheses use classical assumption tests and simple regression analysis. The result was first no significant influence between the application of the investigation e-management to the performance of investigators in criminal matter handlers. Second, there was a significant influence between organizational cultures on investigator performance in criminal matter handlers. And the last was a significant influence between the application of investigation e-management and organizational culture together on the performance of investigators in criminal cover handling.